Efficient PAPR reduction technique in OFDM system using amplitude clipping and selective filtering - M., Supriya; R., Sukumar (Institute of Advanced Engineering and Science, 2025)
One of the most important transmission methods for the next generation of wireless communication systems is orthogonal frequency division multiplexing (OFDM). Transmitting an OFDM signal in a noisy environment with a low bit error rate (BER) is the primary goal. High peakto-average power ratio (PAPR) at the transmitter, which lowers the transmission peak power, is one of OFDM's biggest drawbacks. In this paper, we propose efficient PAPR reduction technique in OFDM system using amplitude clipping and selective filtering. The efficient multiefficiency PAPR reduction strategies with pulse amplitude modulation (PAM) and quadrature amplitude modulation (QAM) modulation are employed with selective filtering and evaluated in terms of percentage reduction level to lowest PAPR of 3.841 db. It is observed that QAM modulation produces better results compared to PAM modulation with less BER of 0.003 for signal-to-noise ratio (SNR) of 20 db.